Nonlinear functional analysis in Banach spaces and Banach algebras : fixed point theory under weak topology for nonlinear operators and block operator matrices with applications /: fixed point theory under weak topology for nonlinear operators and block operator matrices with applications. (2015) - Jeribi, Aref; Krichen, Bilel
No abstract available